Application of Lean Manufacturing Tools to increase Productivity in a cleaning products manufacturing company (LACCEI, 2024)
The main objective of this research was to apply Lean Manufacturing tools to increase productivity at Clorimax E.I.R.L., whose economic activity is the production of cleaning supplies. For which, Lean Manufacturing tools were used such as: The Ishikawa diagram, facilitated the diagnosis and identification of the main factors that affect not having a standardized system and the lack of motivation of the operators in the production area on the other hand, the 5S method made it easier to improve the organization's environment, and finally, the TPM served as a tool to improve the efficiency of equipment and machines. Obtaining as a result an increase in the level of productivity in the organization, going from 2.39 to registering 2.50 soles sold / soles invested, which shows an advance of 4.6%.